2017
DOI: 10.1007/978-3-319-56194-3
|View full text |Cite
|
Sign up to set email alerts
|

International Perspectives on Psychotherapy

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. The publisher, the authors and the editors are safe to assume that the advice and information in this book are believed to be true and accurate at the date of publication. Neither the publisher nor the authors or the editors give a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 254 publications
0
3
0
1
Order By: Relevance
“…In China, it is estimated that about 100 million people suffer from various mental disorders, and 16 million are severely affected by their conditions. Research showed that Asians, especially those of Chinese descent are less likely to report their negative mood than individuals from Western cultures ( 42 , 43 ). Not willing to approach for help could lead to a lower reporting rate for depression.…”
Section: Resultsmentioning
confidence: 99%
“…In China, it is estimated that about 100 million people suffer from various mental disorders, and 16 million are severely affected by their conditions. Research showed that Asians, especially those of Chinese descent are less likely to report their negative mood than individuals from Western cultures ( 42 , 43 ). Not willing to approach for help could lead to a lower reporting rate for depression.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, however, clinical psychology and psychological treatment are two independent professional fields. In Germany, for example, clinical psychology represents an academic-scientific subject and (psychological) psychotherapy is its application in practice (Kryspin-Exner et al, 2017). The great diversity and heterogeneity demonstrated in this overview underlines the importance of the goal of CPE's section "Politics and Education": Accomplishing transparency and clarity about the political and educational situation regarding clinical psychology and psychological treatment in Europe.…”
Section: Conclusion and Consequencesmentioning
confidence: 95%
“…Accordingly, clinical psychology in Europe is characterized by diversification rather than by convergence and agreement. Even neighboring countries, such as the Nordic countries or German-speaking ones, which in some cases cooperate very closely at university level, differ significantly in postgraduate education and their respective professional status (EC, 2016;Karayianni, 2018;Kryspin-Exner, Kothgassner, & Felnhofer, 2017). Further substantial differences can be found in the relationship and differentiation between clinical psychology and psychological treatment (Van Broeck & Lietaer, 2008).…”
mentioning
confidence: 99%
“…contribuições dele foi a valorização da objetividade dentro do método de pesquisa, diminuindo o peso das explicações causais estritamente mentalistas para o comportamento 9 , sublinhando a importância da criação de conceitos operacionais observáveis como os de estímulo, resposta e reforçamento (Hofmann, 2017;Kahhale, 2002), algo que influenciou sobremaneira os trabalhos de Skinner, o mais celebrado behaviorista de todos os tempos. Sobre ele e sua obra, Huxley (1959Huxley ( /2016 Como veremos mais adiante, Skinner apresenta uma visão mais abrangente do que essa, considerando as susceptibilidades espécie-específicas (aspectos inatos/ filogenéticos) e um papel ativo do organismo na alteração dos ambientes em que opera, sendo o comportamento fruto da história filogenética, ontogenética e cultural (Skinner, 1981).…”
Section: O Que é Comportamento?unclassified